PENGARUH FASHION HIJAB TERHADAP PERILAKU KONSUMTIF MAHASISWI FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN PALANGKA RAYA - Sa'adatunnisa Sa'adatunnisa (AL-QARDH, 2016)
Development of the world fashion at this time theis always increased. It can be demonstrated with the development of fashion hijab at this time. Many models are evolving hijab cause excessive purchasing behavior. Such behavior is the consumer behavior, is behavior that purchase goods or services in excess. For this study will focus on the effect on consumer behavior fashion hijab of student IAIN Palangkaraya to determine the effect on consumer behavior fashion hijab of student IAIN Palangkaraya with technique Product Moment Correlation analysis using SPSS 18.0 version. This research is a quantitative descriptive research type ex post facto, the authors use the data collection methods of observation and questionnaires. From the test results performed on the instrument 15 respondents with 24 items declared valid question and can be used to collect the data in the study sample. The population in this study are all mahasiwi Faculty of Economics and Business Islam IAIN Palangkaraya, while the sample amounted to 68 respondents student of the Faculty of Economics and Business Islam IAIN Palangkaraya and from the number of respondents were given a questionnaire to be answered. While the technical data analysis techniques used are product moment correlation analysis. Results of research techniques Pearson product moment correlation (r) shows that the correlation between Fashion hijab with the consumer behavior of 0.780. Based on the interpretation of the correlation coefficient r value , then 0.780 including the level of relations "strong". This shows that there is a strong relationship between fashion hijab with the consumer behavior . Moreover , the significance of the hijab fashion variable (X) and consumer behavior variable (Y) is 0,000. Based on the decision rules of the hypothesis , the probability value of 0.05 is greater than or equal to the probability value Sig . Or (0.05 ≥ 0.000) , then Ho is rejected and Ha accepted, meaning significantly. And the influence of fashion hijab on consumer behavior amounted to 60.9 % , while the remaining 39.1 % is influenced by other factors.